New keynesian phillips curve (NKPC) in newly industrialized countries (NICS) - Lai, Chin Sian (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The NKPC has become popular as a theory for understanding the inflation dynamics and become a popular adopted research topic in evaluating its empirical performance. Despite wide research of NKPC on developed countries, less study have been done in developing countries, especially on countries that are moving forward to industrialized economy. This study is dedicated to the estimation of NKPC in NICs using generalized method of moments (GMM), in which the expected inflation rate is examined by actual value. The main finding in this study is that the NKPC fits NICs data relatively well. The output gap and expected inflation rate do contribute to the inflation dynamics in NKPC model. The results in this study also indicated that the estimated NKPC has been relatively stable over sample period.